The reasons for intellectual differences from the perspective of Islamic law, and the role of Saudi universities in confronting them - Abd El Halim, Sekina Mohamed Mohamed; Ghazy, Amal Abdelaziz Mohamed (Arab Journal for Sciences and Research Publishing, 2023)
The research deals with the causes of intellectual differences and the role of Saudi universities in confronting them, as the research stressed the importance of the university's role in confronting intellectual differences, and spreading a culture of acceptance of the other, and the study followed the descriptive analytical, and documentary approach, for its suitability to the objectives of the research and its nature, where the research deals with a societal phenomenon, and methods of treatment by describing and interpreting it, and then analyzing this phenomenon, to reach ways to treat it by determining the role of each of the common elements in treatment. Through the introduction, which includes a reading of the concepts and terms related to this topic, and two sections, the first dealt with the intellectual differences between causes and manifestations, and the second section dealt with the role of the university in addressing the phenomenon of intellectual differences, explaining the foundational role and the therapeutic role and referring to the pivotal role of the university professor in addressing this phenomenon, then a presentation of the summary and results. Among the most important of them is that avoiding fanaticism and spreading a culture of acceptance of the other is one of the reasons for the unity of society, and limiting the external and internal causes of intellectual differences to facilitate their treatment, the importance of the role of the university and the university professor in treating this phenomenon, and then the most important recommendations, The most important of which are: the university's launch of research projects, to urge students to provide innovative solutions to confront intellectual differences, and supporting Saudi universities for cultural and intellectual exchange between them, and Arab, and international universities by exchanging visits in the form of cultural weeks.
Keywords: differences; intellectual; Saudi universities; Islamic law; role